Multi-stakeholder partnership in smallholding dairy farming : a case study from Bangladesh - Bilkis, Farjana (SLU/Dept. of Economics, 2019)
In the era of Sustainable Development Goal 2030 agenda, development of agribusiness and poverty eradication is quite significant challenges, particularly in developing countries like Bangladesh. Smallholding dairy farming is a crucial part of agribusiness and poverty reduction in Bangladesh, though there are many economic and social challenges for smallholding farmers. Therefore, the smallholding dairy farming industry needs combined, coordinated, and comprehensive support from the government, private sector, and civil society in Bangladesh to form a formal market which may eradicate the social and economic challenges of smallholding farmers. This study reveals how the multi-stakeholder partnership (MSP) approach creates value for smallholding dairy farming business in Bangladesh and what are the consequences of adopting creating shared value (CSV) approach on smallholding dairy farmers. This study also reveals why MSP and CSV approach can be considered as essential business strategy tools to form a structured market for the economic and social development of the smallholding farmers. In this qualitative in-depth case study of smallholding dairy farming in Bangladesh, the researcher identified the economic and social problems of the small-scale dairy business and followed previous literature to find out the experts’ evidence-based opinion as empirical research background. Afterward, the researcher investigated the case from Bangladesh, which adopted the MSP and CSV approach to finding out the features, importance, and evaluation of MSP and CSV. From the literature review, conceptual framework and empirical data from semi-structured interviews of multiple stakeholders, the researcher have found that MSP and CSV execute crucial roles in addressing social and economic challenges of smallholding dairy business. These approaches enable the stakeholders of smallholding dairy business to work together for mutual benefits, to form a formal value chain and to increase profit for all stakeholders. The findings contribute to the literature of business strategy and agribusiness marketing in a developing country. The study is concluded by outlining these findings and suggesting potential avenues for further research.